Phenomenon of Kinetic Energy and Inertia of Material Bodies (Global Journal of Science Frontier Research, 2018)
It is well known that for accelerating the material bodies it is necessary to spend energy, in this case the executed work passes into the kinetic energy. With the braking the body returns this energy to the surrounding bodies, for which required the forces, the reverse facts, which accelerated body. This is the phenomenon of the inertia. However, nature of this phenomenon was up to now not clear. In the article it is shown that the inertia and kinetic energy of material bodies are the consequence of the dependence of the scalar potential of charge on the speed. Are obtained the conversions pour on, which reflect this law.
Keywords: charge; inertia; kinetic energy; scalar-vector potential